Accuracy of clinician gestalt in diagnosing appendicitis in children presenting to the emergency department. (21st January 2019) - Lee, Wei Hao; O'Brien, Sharon; Skarin, Dmitry; Cheek, John A; Deitch, Jessica; Nataraja, Ramesh; Craig, Simon; Borland, Meredith L; ,
Abstract: Objective: Abdominal pain is a common paediatric presentation to the ED. Accurate diagnosis of acute appendicitis is challenging, with the best‐performing clinical scoring systems having sensitivities between 72% and 100%. The aim of this study is to assess the diagnostic accuracy of clinician gestalt according to seniority in diagnosing paediatric acute appendicitis in ED. Methods: This is a prospective multi‐centre observational study of clinician's prediction of appendicitis in children under the age of 16 years presenting to four EDs with abdominal pain over a 1 month period at each site. Clinician‐estimated likelihood of acute appendicitis was compared with the final diagnosis determined by histopathology or operative findings and supplemented by telephone follow up for those without an operation. The primary outcome was diagnostic accuracy of clinician gestalt according to clinician seniority in diagnosing appendicitis. Results: There were 381 children enrolled with completed clinician questionnaires, and 224 children had complete follow up or underwent appendicectomy. The median age was 9 years (interquartile range 6–12) and the incidence of appendicitis was 31/224 (13.8%, 95% confidence interval 9.3–18.4). The area under the curve (AUC), sensitivity, specificity, positive predictive value and negative predictive value of clinician gestalt were 0.84 (0.76–0.91), 81% (63–93%), 76% (69–82%), 35% (28–42%) and 96% (92–98%), respectively, giving an overall diagnostic accuracy of 76% (70–82%). AUC stratified by clinician seniority (junior, intermediate and senior) were 0.89 (0.80–0.98), 0.82 (0.69–0.95) and 0.76 (0.56–0.96), respectively. Conclusions: The diagnostic accuracy of ED clinician gestalt in paediatric appendicitis is comparable to current clinical scoring systems irrespective of seniority.